Peningkatan Kemampuan Menulis Teks Diskusi Menggunakan Media Video Program Gelar Wicara Indonesia Lawyers Club pada Siswa Kelas IX MTs Negeri 6 Aceh Utara - Jannah, Rayhanun; Sundana, Lina; Istiqamah, Istiqamah (Tematik: Jurnal Penelitian Pendidikan Dasar, 2025)
This research aims to explain and describe the improvement in the ability to write discussion texts using the Indonesia Lawyers Club video media among students at MTsN 6 North Aceh. This research uses a qualitative approach with the type of classroom action research (PTK). The research data is in the form of sentences in discussion texts resulting from research subject (MTsN 6 North Aceh) on the activities and learning outcomes of discussion texts using video learning media from the Indonesia Lawyers Club speech program. Research data collection was carried out using test techniques. Data analysis used descriptive statistical techniques. The research results showed that the initial test was 67,23 or 35% of research subjects who achieved the KKM score (73), while the research results in cycle I were 65% of the research subjects succeeded in achieving the KKM with an average of 69,94 (rounded to 70). Futhermore, the results of the research in cycle II were 88% of the research subjects succeeded in achieving the KKM with average score of 79,70 (if rouded to 80), so that this research succeeded in achieving the PTK success criteria.